Influencia de los hábitos alimenticios en el rendimiento académico de los estudiantes de iii, v, vii y ix ciclo de la e.a.p. de trabajo social, facultad de ciencias sociales - universidad nacinal de trujillo, año 2014. - Sebastian Reyes, Rosa Esther (2014)
This research has studied the influence of dietary habits in the academic performance of students of III, V, VII and IX CAS cycle Social Work, Faculty of Social Sciences - National University of Trujillo, during the year 2014. For purposes of this study, the research conducted was descriptive the same that allowed characterizing the variables taken into account with respect to food habits in academic performance. For this he had a sample of 50 users of the Professional Academic School of Social Work at the National University of Trujillo, which part of your daily life consists of eating habits of which are reflected in the academic performance of students Social Work. According to the results obtained in this investigation, generally it was observed that most of the students always relate to both academic achievement and eating habits go hand in hand, causing concern about the power of the day day, but sometimes this is put aside for economic reasons, lack of time, etc, so that although it is an issue of great importance in terms of eating habits that make the eating habits of young students, and which are essential parts for its own student conduct; and taking responsibility for their food, so it becomes a critical stage in the development of eating habits, which will affect their health and their performance but in the matter is taken. For that reason it is important to consider the influence this has on the eating habits because we are what we eat and part of it is influenced by the level of performance and mental burden of students, which is why you see on the need to work together towards the improvement in the power consumed by social work students